Pharmacogenetic meta-analysis of genome-wide association studies of LDL cholesterol response to statins - Postmus, I; Trompet, S; Deshmukh, H; Barnes, MR; Li, X; Warren, H; Chasman, D; Zhou, K; Arsenault, B; Donnelly, L; Wiggins, K; Avery, C; et al. (Springer Nature, 2014)
Statins effectively lower LDL cholesterol levels in large studies and the observed interindividual response variability may be partially explained by genetic variation. Here we perform a pharmacogenetic meta-analysis of genome-wide association studies (GWAS) in studies addressing the LDL cholesterol response to statins, including up to 18,596 statin-treated subjects. We validate the most promising signals in a further 22,318 statin recipients and identify two loci, SORT1/CELSR2/PSRC1 and SLCO1B1, not previously identified in GWAS. Moreover, we confirm the previously described associations with APOE and LPA. Our findings advance the understanding of the pharmacogenetic architecture of statin response.